(untitled) (Nepalese Veterinary Journal, 2017)
The aim of this study was to establish the reference values for hematology and serum biochemistry of pre-parturient Murrah crossbred buffaloes of Western Chitwan (Bharatpur Metropolitancity). The study was cross-sectional in which31 apparently healthy pregnant Murrah cross buffaloes ranging from 5-8 years were selected randomly after confirmation by rectal palpation. Blood samples collected from jugular vein were stored in EDTA tubes for hematological analysis and for biochemical analysis centrifuged at 1500 rpm for 20 minutes to separate serum after 1 hour of collection. Hematological indices were determined manually using routine laboratory techniques and serum biochemicals were analysed using automated analyzer (Dimension RXL). Serum biochemicals like Glucose, BUN, Creatinine, Calcium, Phosphorous, Magnesium, AST, ALT, total serum Protein and albumin level were found within the normal range. Similarly, hematologic indices Hb, PCV, Platelet counts, RBC counts, WBC counts, and differential leukocyte counts were also in normal ranges. However, eosinophil (7.83±0.82), and monocyte (4.4±0.53) counts were higher at significant numbers which suggests gastrointestinal parasitic infestations and/or allergic diseases along with some chronic infectious diseases in the buffalo herd of Bharatpur Metropolitancity in western Chitwan.